2016
DOI: 10.1186/s12864-016-3347-1
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent sequences disclose potential for intra-genomic dispersal of satellite DNA repeats and suggest a complex network with transposable elements

Abstract: BackgroundSatellite DNA (satDNA) sequences are typically arranged as arrays of tandemly repeated monomers. Due to the similarity among monomers, their organizational pattern and abundance, satDNAs are hardly accessible to structural and functional studies and still represent the most obscure genome component. Although many satDNA arrays of diverse length and even single monomers exist in the genome, surprisingly little is known about transition from satDNAs to other sequences. Studying satDNA monomers at junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 59 publications
6
47
0
Order By: Relevance
“…In contrast to TEs, satDNAs do not have the ability to transpose by themselves. However, there are some reported examples showing that TEs may act as a substrate for satDNA emergence and mobility ( Dias et al 2015 ; Meštrović et al 2015 ; Satović et al 2016 ). We created a database containing the 500-bp sequences immediately before and after each CDSTR198 array (37 in total; Table S6 in File S1 ) found in the assembled scaffolds of D. buzzatii .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to TEs, satDNAs do not have the ability to transpose by themselves. However, there are some reported examples showing that TEs may act as a substrate for satDNA emergence and mobility ( Dias et al 2015 ; Meštrović et al 2015 ; Satović et al 2016 ). We created a database containing the 500-bp sequences immediately before and after each CDSTR198 array (37 in total; Table S6 in File S1 ) found in the assembled scaffolds of D. buzzatii .…”
Section: Resultsmentioning
confidence: 99%
“…SatDNAs do not have the ability to transpose by themselves as transposable elements (TEs) do. However, there are some reported examples showing that TEs may act as a substrate for satDNA emergence and mobility ( Dias et al 2015 ; Meštrović et al 2015 ; Satović et al 2016 ).…”
mentioning
confidence: 99%
“…Conversely, tandem repeats have also been found as integral components of TEs [ 109 ] and some satDNA were probably derived from tandem repeats present in a hypothetical miniature inverted–repeat transposable element (MITE)-like element [ 109 , 110 , 111 , 112 ]. Thus, it has been suggested that mobile elements may be an important source of satDNAs in diverse genomes [ 109 , 113 , 114 , 115 ].…”
Section: Changing Conceptsmentioning
confidence: 99%
“…5D). The repetitive region of the consensus map displays 22 labels; however, as the first or last repeat may be truncated and unlabeled (Dini and Lipsick 1993;Satovićet al 2016), these 22 labels indicate 22 ± 1 D4Z4 repeats. The exact size of the array can be validated by measuring the length of the array directly from the consensus map.…”
Section: Simultaneous Quantification Of Copy Number and Methylation Smentioning
confidence: 99%